2023
DOI: 10.3390/biomedicines11102655
|View full text |Cite
|
Sign up to set email alerts
|

The Value of CXCL1, CXCL2, CXCL3, and CXCL8 as Potential Prognosis Markers in Cervical Cancer: Evidence of E6/E7 from HPV16 and 18 in Chemokines Regulation

Leonardo Fernandez-Avila,
Aribert Maryosly Castro-Amaya,
Andrea Molina-Pineda
et al.

Abstract: Cervical cancer (CC) is a serious global health issue, and it is well-known that HPV infection is the main etiological factor that triggers carcinogenesis. In cancer, chemokine ligands and receptors are involved in tumor cell growth, metastasis, leukocyte infiltration, and angiogenesis; however, information on the role played by E6/E7 of HPV16/18 in the modulation of chemokines is very limited. Therefore, this study aimed to determine whether chemokines are differentially expressed in CC-derived cell lines; if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…HPV’s carcinogenic potential is driven by its E6 and E7 oncoproteins [ 21 , 23 , 24 , 25 ]. These proteins provoke uncontrolled cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…HPV’s carcinogenic potential is driven by its E6 and E7 oncoproteins [ 21 , 23 , 24 , 25 ]. These proteins provoke uncontrolled cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The human CC cell lines SiHa, HeLa, and C33A were obtained from the Centro de Investigación Biomédica de Occidente (CIBO) (Guadalajara, México), kindly provided by Ph.D. Adriana Aguilar Lemarroy from the cell bank of the CIBO Immunology Division [27]. Primary fibroblasts were acquired from the Escuela Nacional de Ciencias Biológicas (ENCB-IPN) (Cdmx, México).…”
Section: Cell Lines and Culturementioning
confidence: 99%
“…To discern the molecular process engaged in the viral immune escape, it has been shown that infection with HPV16 inhibits the expression of TLR9 by E6 and E7, resulting in the downregulation of inflammatory cytokines like type-1 IFNs and inhibition of immune responses [ 76 ]. In addition, the study on HPV E6 and E7 in cervical cancer found that they regulate the expression of CXCL1, CXCL2, and CXCL3, as well as CXCL8 chemokines [ 77 ]. Therefore, the immune system targets viral oncogenes expression through OS; however, excessive OS may facilitate HPV DNA integration [ 78 ].…”
Section: Introductionmentioning
confidence: 99%